2020
DOI: 10.1002/leg3.52
|View full text |Cite
|
Sign up to set email alerts
|

Kidney bean (Phaseolus vulgaris) starch: A review

Abstract: The mini review focuses on the morphology, pasting, rheological and in vitro digestibility of kidney bean starch. In legumes seeds, starch is the most abundant carbohydrate reserve in plants and have been ascribed medicinal and cultural as well as nutritional roles. The major carbohydrate of kidney bean seeds is starch, which accounts for 25–45% of the dry matter. Lower swelling and high solubility of kidney bean starches indicate their higher functional properties than cereal starches. High amount of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…A set of GH(s) connected to starch degradation has been identi ed and includes GH13 and GH65 representatives. This nding is in line with the fact that starch is the major carbohydrate present in beans and B. coagulans MA-13 was isolated from a canned beans manufacturing process [5,26]. Three GHs members belonging to families 18 and 73 are related to the sporulation pathways of B. coagulans.…”
Section: Annotation Of Glycosyl Hydrolasessupporting
confidence: 72%
“…A set of GH(s) connected to starch degradation has been identi ed and includes GH13 and GH65 representatives. This nding is in line with the fact that starch is the major carbohydrate present in beans and B. coagulans MA-13 was isolated from a canned beans manufacturing process [5,26]. Three GHs members belonging to families 18 and 73 are related to the sporulation pathways of B. coagulans.…”
Section: Annotation Of Glycosyl Hydrolasessupporting
confidence: 72%
“…Alpha-D-glucopyranosyl linked with α-D- (1–4) or α-D- (1–6) linkages are the basic units of starches, which are composed of amylose and amylopectin ( 72 , 73 ). Previous studies have shown that the abundant RS in legumes is associated with postprandial blood glucose content, contributing to a positive effect on type 2 diabetes ( 74 , 75 ). In the present study, the proportions of RS to TS in adzuki beans ranged from (69.78 ± 2.45%) to (81.03 ± 0.06%), which was higher than the results reported by previous studies ( 38 , 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through an energy-dependent process, glucose molecules accumulate to form starch. Sugars are mainly stored in the form of starch [ 71 ] because greater energy can be packed into a smaller space in starch molecules compared with sucrose or glucose molecules; moreover, starch molecules can release this energy easily, thereby maximizing both mobilization and storage. Nucleotide sugars, e.g., UDP-glucose, can combine with fructose-6-phosphate and be stored in the form of galactomannans and mannans through a series of biochemical reactions.…”
Section: Sucrolytic Route Leading To Seed Storage Reserve Biosynthesismentioning
confidence: 99%